OPTIMALISASI PERAN APARAT PEMERINTAH DALAM PEMBENTUKAN PERATURAN DESA YANG PARTISIPATIF UNTUK MENDUKUNG PENGUATAN DESA TANGGUH BENCANA DI DESA SOGINTI KECAMATAN PAGUAT KABUPATEN POHUWATO - Rahim, Erman; Amrain, Fitran (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Soginti Village located in Paguat District, Paguat District, Pohuwato Regency in 2024 was affected by a natural disaster, namely a flood that harmed residents. In order to overcome this, proper handling is needed through the formation of village regulations. The purpose of this activity is to develop innovative work results that have utility value and benefits for the wider community, improve the quality of research and community service in the Gorontalo State University environment which is superior and competitive and ready to face global challenges. Implementation method. Implementation method The activity was carried out through the Real Work Lecture (KKN) program which is an activity based on Community Service in Soginti Village through mentoring, workshops and tree planting. The results of the implementation of this community service, namely KKN, have implemented 3 work programs, namely the creation of Disaster Resilient Village Regulations, Workshops on optimizing the role of government officials in the formation of participatory village regulations to support the strengthening of disaster resilient villages and Planting of living kitchens. The program implemented in Soginti Village received support from the government and community members so that it could run well.